The Fall of Ufology: Don’t Bother Me with Your Deceit by Geoffrey B. Cox - Alexander, John B. (Journal of Scientific Exploration, 2021)
This self-published book is clearly the product of a frustrated researcher. The subtitle alone provides an accurate insight into Cox’s thinking. That said, anyone who has been around these fields for any length of time can share a sense of frustration. Listening to any number self-anointed experts, and even charlatans, who populate the fields of the paranormal, can be exasperating. Yes, tall tales abound. Unfortunately, there are no lower limits to crazy that will not attract a following. Such is the nature of studying unexplained phenomena. The publication does not appear to have been professionally edited, as one finds both grammatical and contextual errors. Cox contracted with a company called Outskirts Press; one that specializes in physically printing self-published books. In checking with them, I found they do offer an editing service. The author would have been better served to have paid for that option, as there are many incomplete sentences and other grammatical errors. As an established author, I believe attempting to edit your own material is fraught with danger. That is the position I believe most frequently published and serious authors would agree with. Mechanically speaking, The Fall of the Ufology appears to be designed for an e-publication, as opposed to a print format. That is because there are many Internet sites that are listed and that I suspect can be directly accessed in electronically published form. The contextual format changes significantly throughout the book. Some of it is straight nonfiction statements of fact, but that is often followed by side commentary as if one were attending a social gathering. While the title implies the singular topic is UFOs, it digresses into many other areas. He takes significant liberties in defining, or redefining, terms that have been around for many years, even centuries. Seemingly, Cox does view himself as the arbiter of acceptability of terms. As an example, he proffers “Anomalogy” as a new term which he defines “as a person who studies anomalies,” as opposed to parapsychology or ufology. In many ways, what Cox puts forth many of us would view as a blinding flash of the obvious. The notion of the interrelationship between various fields in the study of phenomena has been addressed for decades. Several authors, including Jacques Valle and myself, have written extensively on this matter. On a hypocritical note, Cox simultaneously admonishes Ufologists who present outlandish opinions at conferences, and then destroys his own credibility by accepting extreme conspiracy theories. While addressing his own UAP (unidentified aerial phenomena) sightings, he states that he believes the craft as being of man-made origin. That, even though he witnessed events that would be beyond our currently known technical capabilities. Specifically, on page 32 he states, “I believe now that somehow we on earth have been given this technology from ‘Outside Intelligence.’” Here, I am admittedly biased, but have explicitly eliminated that possibility in my own UFO writings. The notion that the US government has reverse-engineered a crashed UFO is not new. But as I have pointed out, if such technology existed, making small craft that flit about would be trivial compared to the fundamental understanding of an entirely new energy source. Such a capability would undeniably alter our strategic interests and geopolitical landscape forever.